2018
DOI: 10.1002/anie.201810082
|View full text |Cite
|
Sign up to set email alerts
|

The In Situ Sulfidation of Cu2O by Endogenous H2S for Colon Cancer Theranostics

Abstract: Expression of a high concentration of H2S is closely related to the formation of colon cancer tumors. However, only a few H2S‐triggered theranostics agents for colon cancer have been reported to date. Now, a turn‐on theranostics agent was developed by utilizing the in situ reaction of Cu2O and endogenous H2S at colon tumor sites. Based on in vitro and in vivo experiments, excellent photoacoustic imaging and photothermal therapy were both confirmed by this in situ reaction‐activated colon cancer theranostics me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
114
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(115 citation statements)
references
References 29 publications
0
114
0
1
Order By: Relevance
“…In contrast, the absorption intensity at 808 nm of triggered Au@Cu 2 O changed significantly even at very low concentrations, NaHS (<0.4 × 10 −3 m ) and Au@Cu 2 O (0.3 × 10 −3 m ) as shown in Figure b and Figure S6d in the Supporting Information. The strong Au@Cu 2 O+NaHS absorbance at low concentration indicated that the injection dose can be reduced to a very low concentration compared with our previous report . The interfering substance, including common ions and amino acids, was used to evaluate the interference factors for the NaHS‐triggered Au@Cu 2 O.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…In contrast, the absorption intensity at 808 nm of triggered Au@Cu 2 O changed significantly even at very low concentrations, NaHS (<0.4 × 10 −3 m ) and Au@Cu 2 O (0.3 × 10 −3 m ) as shown in Figure b and Figure S6d in the Supporting Information. The strong Au@Cu 2 O+NaHS absorbance at low concentration indicated that the injection dose can be reduced to a very low concentration compared with our previous report . The interfering substance, including common ions and amino acids, was used to evaluate the interference factors for the NaHS‐triggered Au@Cu 2 O.…”
Section: Resultsmentioning
confidence: 85%
“…The other AOAA+Au@Cu 2 O and SAM+Au@Cu 2 O mice were treated one with, aminooxyacetic acid (AOAA, an endogenous H 2 S inhibitor) and the other with S ‐adenosyl‐L‐methionine (SAM, an endogenous H 2 S promoter) prior to intravenous injection of Au@Cu 2 O. In order to demonstrate that the enhanced performance of Au@Cu 2 O as a result of the coupling effect can improve the contrast, the injected dose of Au@Cu 2 O is 2.5 mg kg −1 , which is much lower than 6 mg kg −1 used for Cu 2 O in our previous report . The photoacoustic images of mice were collected before (control) and between 1 and 8 h after treatment (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations